Penerapan Metode Iqra Dalam Pembelajaran Al-qur'an: Application of the Iqra Method in Learning the Qur'an - Abdul Malik Iskandar; Syamsu K; Haslinda B. Anriani; Muhammad Masdar (JOURNAL OF TRAINING AND COMMUNITY SERVICE ADPERTISI (JTCSA), 2022)
This article aims to describe the iqra method in learning the Koran at a TPA in Makassar city. The Iqra method is a very easy reading method and attracts the interest of many teachers to apply it in the santri group. This dedication method is to apply the method in teaching and see the speed at which students know letters compared to other methods. The results of this service are obtained as follows: this iqra method makes students read the Koran faster than other methods because students learn more while singing and reading is still good according to the name. The recommendation for this service is that the Iqra method is more suitable for the beginner age of children learning the Koran which is full of games and enjoys doing it.